Science Studies Elsewhere: The Experimental Life and the Other Within. (3rd March 2016) - Hofmänner, Alexandra
Abstract : This study is concerned with current images of Science Studies travelling to places outside Western Europe and North America. These images focus on the movement of Science Studies' formative concepts and ideas. They eclipse other formative aspects specific to the context in which this field was established. For example, Science Studies has analysed science within the conceptual architecture of modernity. Michel-Rolph Trouillot has proposed the notion of "Elsewhere" as analytical lens to analyse the constitution of modernity. The paper claims that modern science, too, can be studied through this analytical lens to call attention to characteristics of science that remain systematically eclipsed. Trouillot's notion of Elsewhere is applied to a paradigmatic case study from the field of Science Studies—Leviathan and the Air-Pump by Steven Shapin and Simon Schaffer—to test and demonstrate its analytical potential. By proposing a Programme in Science Studies Elsewhere, this paper refers to David Bloor's four tenets for a Strong Programme in the Sociology of Knowledge to consider the implications of this analysis for the study of modern science and for the field of Science Studies.